Locating hope in performance: lessons from Edward Kabuye - Noss-Van Buren, Kathleen J. (International Library of African Music, 2009)
This article draws upon fieldwork in Nairobi, Kenya, and scholarly literature to consider the efficacy of music in communicating messages and promoting social change. I focus on the work of Nairobi-based Ugandan artist Edward Kabuye. Kabuye's projects reveal his approach to life: his creative thinking, his desire to address the problems facing the communities in which he lives, and his perseverance despite myriad challenges. Through performance, Kabuye seeks to persuade audience members to rethink the circumstances of their lives and to take positive action.
Keywords: African Music